Extremum Problem for the Wiener–Hopf Equation - Cherskii, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
The extremum problem for the Wiener–Hopf equation obtained by replacing the condition u(x) = 0, x < 0, by the condition of the minimum of the quadratic functional of the function u(x)exp(−x), −∞ < x < ∞, is solved in closed form.